The use of languages as tool to (re)create social and national identities over three generations in Mozambique from 1975 to modern times - Carvalho, X. (Portuguese Studies Review, 2021)
The relationship between language(s) and identities are described by three generations of Mozambicans, in Southern Africa, from 1975 to modern times. How are languages used to (re)create national and social identities in post-colonial Mozambique? Portuguese, the former colonial language, continues to be an identity marker of social and political dominant position in society, particularly in urban settings, giving access to political power and modernity, reinforcing race stereotypes. Conversely, national languages represent social and political resistance described by the 18 life histories collected over three generations, alongside with ethnographic fieldwork done in southern Mozambique. The three generations are divided within a specific historic and ideological setting (i.e., socialism, democracy, and neoliberalism). The periods are based upon the notion of generation understood as a space and time of identity and political construction, in which biography and history meet. In addition, a gender approach is also described with different identity outcomes and strategies.